GREENING THE COMPANY'S FLEET - Jež, Sandra; Šinko, Simona; Knez, Matjaž; Obrecht, Matevž (Journal of Applied Engineering Science, 2017)
Transport is responsible for 30 % of all greenhouse gas emissions in Slovenia. Companies specialized in transport are challenged with seeking solutions how to reduce the pollution from their fleets on one side and reducing costs and increasing efficiency on the other. Greening the companies fleets is in rise all over the world. Beside reducing the costs the environmental issues such as carbon footprint is becoming more and more important for company's image. This paper is based on a research study of company Avtosteklo d.o.o. Their primary activity is replacement of windscreens on vehicles which is often done at customers’ homes or at their work places therefore company owns a fleet of 24 vehicles in 5 branches across Slovenia with huge amount of annually driven kilometres and consequently high carbon emissions. Calculations on their current fuel costs and released carbon dioxide were examined and cross-compared. Results showed that 78,9 tons of carbon dioxide is released in one month of their operations. Main goal of this paper is therefore to present possible positive effects of replacement of conventional vehicles with alternative ones. After reviewing and analysing several possibilities we have suggested replacement of conventional cars with electric ones as a long term solution since they don't release carbon dioxide in use phase. In order to identify the best solutions we have proposed also replacement of vehicles for long relations with vehicles on compressed natural gas. The study also showed significant impacts on reduction of fuel costs and vehicles maintaining.
Keywords: Avtosteklo Ltd; Sustainable transport; Green fleet; CO2; Emissions; Alternative fuel vehicles